IGF-IR Targeted Therapy: Past, Present and Future - Janssen, Joseph A. M. J. L.; Varewijck, Aimee J. (Frontiers in Endocrinology, 2014)
The IGF-I Receptor (IGF-IR) has been studied as an anti-cancer target. However, monotherapy trials with IGF-IR targeted antibodies or with IGF-IR specific tyrosine kinase inhibitors has, overall, been very disappointing in the clinical setting. This review discusses potential reasons why IGF-I R targeted therapy fails to inhibit growth of human cancers. It has become clear that intracellular signaling pathways are highly interconnected and complex instead of being linear and simple. One of the most potent candidates for failure of IGF-IR targeted therapy is the insulin receptor isoform A (IR-A). Activation of the IR-A by insulin-like growth factor-II (IGF-II) bypasses the IGF-IR and its inhibition. Another factor may be that anti-cancer treatment may reduce IGF-IR expression. IGF-IR blocking drugs may also induce hyperglycemia and hyperinsulinemia, which may further stimulate cell growth. In addition, circulating IGF-IRs may reduce therapeutic effects of IGF-IR targeted therapy. Nevertheless, it is still possible that the IGF-IR may be a useful adjuvant or secondary target for the treatment of human cancers. Development of functional inhibitors that affect the IGF-IR and IR-A may be necessary to overcome resistance and to make IGF-IR targeted therapy successful. Drugs that modify alternative downstream effects of the IGF-IR, so called “biasing agonists”, should also be considered.